A gamified choice experiment of traditional African vegetable varieties in West Africa - Sidol Houngbo; Simon Codjo; Mathieu A. T. Ayenan; Rodrigue S. Kaki; Benoît Govoeyi; Modeste Dohou; Christelle Komlan; Irene M. Mitchodigni; N'Danikou Sognigbe; Maarten van Zonneveld; Pepijn Schreinemachers (PLoS ONE, 2026)
Understanding trait preferences of value chain actors is essential for designing demand-driven breeding programs for traditional African vegetables (TAVs). The objective of this study was to assess the varietal preferences of farmers, traders, and consumers for amaranth, okra, and jute mallow in Benin and Mali. We employed a gamified choice experiment, following the Bradley–Terry model and recursive partitioning, to identify preference patterns and segment participants by country, age, and gender. Different preference patterns appeared across segments, showing clear social and geographic diversity in varietal needs. Traders and consumers consistently focused on market and organoleptic traits, specifically, leaf integrity and taste for amaranth, high mucilage content (viscosity) for okra, and both leaf integrity and viscosity for jute mallow. Farmers prioritized a range of agronomic traits. For okra, farmers specifically valued harvesting duration, disease resistance, and fruit yield per plant, reflecting the crop’s dual role in income generation and nutritional security. Farmers in Mali placed greater emphasis on drought tolerance across all three crops than farmers in Benin. The findings highlight the need for TAV breeding and variety introduction programs to consider not only agronomic performance but also market preferences and organoleptic qualities.